Pediatric Clinical Classification System for Use in Inpatient Settings - Gill, Peter J. (JAMA Pediatr, 2021)
This cross-sectional study assesses the specificity of the Pediatric Clinical Classification System and Healthcare Cost and Utilization Project diagnosis categories for clinical classification in pediatric inpatient settings.